Online Distributed Algorithms for Seeking Generalized Nash Equilibria in Dynamic Environments - Lu, Kaihong; Li, Guangqi; Wang, Long (IEEE transactions on automatic control, 2021)
In this article, we study the distributed generalized Nash equilibrium (GNE) seeking problem of noncooperative games in dynamic environments. Each player in the game aims to minimize its own time-varying cost function subject to a local action set. The action sets of all players are coupled through a shared convex inequality constraint. Each player can only have access to its own cost function, its own set constraint, and a local block of the inequality constraint, and can only communicate with its neighbors via a connected graph. Moreover, players do not have prior knowledge of their future cost functions. To address this problem, an online distributed algorithm is proposed based on consensus algorithms and a primal-dual strategy. The performance of the algorithm is measured by using dynamic regrets. Under mild assumptions on graphs and cost functions, we prove that if the deviation of the variational GNE sequence increases within a certain rate, then the regrets, as well as the violation of inequality constraint, grow sublinearly. A simulation is presented to demonstrate the effectiveness of our theoretical results.